Association of ficolin‐3 with abdominal aortic aneurysm presence and progression. (15th February 2017) - Fernandez‐García, C.‐E.; Burillo, E.; Lindholt, J. S.; Martinez‐Lopez, D.; Pilely, K.; Mazzeo, C.; Michel, J.‐B.; Egido, J.; Garred, P.; Blanco‐Colio, L. M.; Martin‐Ventura, J. L.
Abstract : Essentials Abdominal aortic aneurysm (AAA) is asymptomatic and its evolution unpredictable. To find novel potential biomarkers of AAA, microvesicles are an excellent source of biomarkers. Ficolin‐3 is increased in microvesicles obtained from activated platelets and AAA tissue. Increased ficolin‐3 plasma levels are associated with AAA presence and progression. Summary: Background: Abdominal aortic aneurysm (AAA) patients are usually asymptomatic and AAA evolution is unpredictable. Ficolin‐3, mainly synthesized by the liver, is a molecule of the lectin complement‐activation pathway involved in AAA pathophysiology. Objectives: To define extra‐hepatic sources of ficolin‐3 in AAA and investigate the role of ficolin‐3 as a biomarker of the presence and progression of AAA. Methods: Microvesicles (exosomes and microparticles) were isolated from culture‐conditioned medium of ADP‐activated platelets, as well as from AAA tissue‐conditioned medium (thrombus and wall). Ficolin‐3 levels were analyzed by western‐blot, real‐time PCR, immunohistochemistry and ELISA. Results: Increased ficolin‐3 levels were observed in microvesicles isolated from activated platelets. Similarly, microvesicles released from AAA tissue display increased ficolin‐3 levels as compared with those from healthy tissue. Moreover, ficolin‐3 mRNA levels in the AAA wall were greatly increased compared with healthy aortic walls. Immunohistochemistry of AAA tissue demonstrated increased ficolin‐3, whereas little staining was present in healthy walls. Finally, increased ficolin‐3 levels were observed in AAA patients' plasma ( n = 478) compared with control plasma ( n = 176), which persisted after adjustment for risk factors (adjusted odds ratio [OR], 5.29; 95% confidence interval [CI], 3.27, 8.57)]. Moreover, a positive association of ficolin‐3 with aortic diameter (Rho, 0.25) and need for surgical repair was observed, also after adjustment for potential confounding factors (adjusted hazard ratio, 1.55; 95% CI, 1.11, 2.15). Conclusions: In addition to its hepatic expression, ficolin‐3 may be released into the extracellular medium via microvesicles, by both activated cells and pathological AAA tissue. Ficolin‐3 plasma levels are associated with the presence and progression of AAA, suggesting its potential role as a biomarker of AAA.